Examining Thailand's Public Health Emergency Management Response to COVID-19: Insights from Health Region 9s Pandemic Approach - Suwanna Bengthong; Preecha Suvarnathong; Suwimon Ukraisa; Kanchana Boonphak; Rungrueng Kitphati; Juraporn Krates; Wilailuk Ruangrattanatrai; Worayuth Nak-Ai (My University, 2024)
This phenomenological study investigated Thailand's public health emergency response during COVID-19 via Health Region 9's "COVID-19 Back Home" program.Indepth interviews with 112 key stakeholders revealed coordination mechanisms, treatment capacities, community participation and behavioral adaptations underpinning perceived successes.However, presentations of rich qualitative insights were limited.Discussion focuses on contextualizing robust infrastructure, public-private collaborations, and social capital evident in pandemic responses while calling for enhanced methodological rigor in future inquiries.
Keywords: Pandemic; 2019-20 coronavirus outbreak; COVID-19 Pandemic Impacts